Peran Supervisi Akademik Kepala Sekolah dalam Optimalisasi Implementasi Kurikulum Merdeka di Sekolah - Wahidah, Asni; Amrulloh, Amrulloh; Hakim, Dhikrul (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2024)
SMA Darul Ulum 2 Unggulan BPPT Jombang has successfully integrated the Merdeka Curriculum effectively, supported by academic supervision practices carried out by the school principal. The purpose of this supervision is to prepare and optimize the implementation of the Merdeka Curriculum, as evidenced by the school's achievements as the best in Jombang and the high number of students accepted through the SNBP. However, there are several challenges in the implementation of supervision, including the presence of teachers who have surpassed retirement age, time limitations, and variations in human resources. This study aims to identify the role of the school principal in academic supervision that supports the implementation of the Merdeka Curriculum, as well as the factors that contribute to or hinder this process. The research method used is qualitative with an interactive approach, and data is collected through observations, interviews, and document analysis. Data analysis is conducted through triangulation, verification, reduction, and systematic presentation. The study's results reveal that the principal's academic supervision encompasses four important aspects: pre-observation, socialization, mentoring, and monitoring. Nevertheless, various obstacles such as teacher age, time constraints, and varying competencies among teachers need to be addressed to enhance the effectiveness of supervision.